The spiritual personal orientation as the factor of character harmonization in adolescence - Natalia V. Pavlyk (Национальный психологический журнал, 2015)
The paper is devoted to the analysis of spiritual determination of character development in adolescence. On the basis of the experimental research of spiritual sphere and the degree of a character harmony of today’s students, the author allocates the psychological laws of influencing the spiritual orientation for the process of character developments in adolescents. The experimental research has shown that spiritual orientation and character harmony are mutually influenced. However, the spiritual potential does not always positively correlate with character harmony as because the process of character harmonization does not appear linear, but cyclic with of rise and fall periods. The fall periods are accompanied by expressed disharmony of character and promotes social psychological personality maladjustment. Conditioned by steady spiritual orientation, spiritual self-development promotes character harmonization through overcoming personal spiritual crises. Continuous moral struggle against imperfection conditioned, the personality faces gradual character harmonization according to the spiritual ideal. Spiritually and creative activity promotes activation of psychological mechanisms of character harmonization in adolescents. The basic directions of optimization of the education system is creating psychological conditions of spirituality and moral improvement, saturation of teaching and educational programs by spiritual and creative contents.